Schaum's outlines : Programming with JAVA - Hubbard, John R.; Hubbard, John R. (New Delhi, Tata McGraw-Hill, 2004)
What could be better than the bestselling Schaum's Outline series? For students looking for a quick nuts-and-bolts overview, it would have to be Schaum's Easy Outline series. Every book in this series is a pared-down, simplified, and tightly focused version of its predecessor. With an emphasis on clarity and brevity, each new title features a streamlined and updated format and the absolute essence of the subject, presented in a concise and readily understandable form. Graphic elements such as sidebars, reader-alert icons, and boxed highlights stress selected points from the text, illuminate keys to learning, and give students quick pointers to the essentials. Designed to appeal to underprepared students and readers turned off by dense text Cartoons, sidebars, icons, and other graphic pointers get the material across fast Concise text focuses on the essence of the subject Delivers expert help from teachers who are authorities in their fields Perfect for last-minute test preparation So small and light that they fit in a backpack! Key Features: Master today's hottest programming language. Completely updated to reflect changes in Java 1.4. Over 200 fully solved problems. Create dynamic animations, simulations, and interactive web pages. About the Author: Jonn R. Hubbard, Ph.D. (Richmond, VA) is Professor of Mathematics and Computer Science at the University of Richmond. He is the author of the popular Schaum's Outline Programming with C++ and Programming with Java. Table of Content: Chapter 1. Getting Started with Java Chapter 2. Strings Chapter 3. Selection Chapter 4. Iteration Chapter 5. Methods
Index 339-345p.
Keywords: Computer Laguage; Computer Science; Programming with JAVA; General Science